Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa - I Putu Suardika (Edukasi: Jurnal Pendidikan Dasar, 2023)
This study aims to determine the increase in learning outcomes of Indonesian language students in class VII.3 of SMP Negeri 1 Amlapura in the odd semester of the 2022/2023 academic year. This research is a PTK research which consists of several cycles. The data collection method used is the test method. After the data is collected, the data analysis used is descriptive quantitative data analysis. This research is said to be successful, if the value of student learning outcomes reaches an average of ≥ 72 with 85% classical completeness and 72% student absorption. Based on the research that has been done, it is concluded that the application of the STAD type cooperative learning model can effectively improve the learning outcomes of Indonesian language students in class VII.3 of SMP Negeri 1 Amlapura Odd Semester in the 2022/2023 Academic Year. This is evidenced by the significant increase in the classical completeness rate, which was 43.75% in the pre-cycle, increased in cycle I to 62.50% and in cycle II increased to 87.50%.